Cholic acid and deoxycholic acid induce skeletal muscle atrophy through a mechanism dependent on TGR5 receptor. Issue 1 (7th June 2020) - Abrigo, Johanna; Gonzalez, Francisco; Aguirre, Francisco; Tacchi, Franco; Gonzalez, Andrea; Meza, María Paz; Simon, Felipe; Cabrera, Daniel; Arrese, Marco; Karpen, Saul; Cabello‐Verrugio, Claudio
Abstract: Skeletal muscle atrophy is characterized by the degradation of myofibrillar proteins, such as myosin heavy chain or troponin. An increase in the expression of two muscle‐specific E3 ligases, atrogin‐1 and MuRF‐1, and oxidative stress are involved in muscle atrophy. Patients with chronic liver diseases (CLD) develop muscle wasting. Several bile acids increase in plasma during cholestatic CLD, among them, cholic acid (CA) and deoxycholic acid (DCA). The receptor for bile acids, TGR5, is expressed in healthy skeletal muscles. TGR5 is involved in the regulation of muscle differentiation and metabolic changes. In this paper, we evaluated the participation of DCA and CA in the generation of an atrophic condition in myotubes and isolated fibers from the muscle extracted from wild‐type (WT) and TGR5‐deficient (TGR5 −/− ) male mice. The results show that DCA and CA induce a decrease in diameter, and myosin heavy chain (MHC) protein levels, two typical atrophic features in C2 C12 myotubes. We also observed similar results when INT‐777 agonists activated the TGR5 receptor. To evaluate the participation of TGR5 in muscle atrophy induced by DCA and CA, we used a culture of muscle fiber isolated from WT and TGR5 −/− mice. Our results show that DCA and CA decrease the fiber diameter and MHC protein levels, and there is an increase in atrogin‐1, MuRF‐1, and oxidative stress in WT fibers. The absence of TGR5 in fibers abolished all these effects induced by DCA and CA. Thus, we demonstrated that CS and deoxycholic acid induce skeletal muscle atrophy through TGR5 receptor. Abstract : Cholic acid and deoxycholic acid, in a form dependent on TGR5 expression, induce an atrophic condition in skeletal muscle fibers, concomitant with increased levels of oxidative stress and protein catabolic pathways.